1976
DOI: 10.1007/bf01638726
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between aminoglycoside antibiotics and carbenicillin or ticarcillin

Abstract: Carbenicillin or ticarcillin were incubated individually with each of the following antibiotics: gentamicin, tobramycin, sisomicin, amikacin. The residual activity of each aminoglycoside in this mixture was assayed enzymatically. Amikacin was inactivated the least of the aminoglycosides. Both penicillins inactivated each aminoglycoside to a similar extent by a degree which varied according to the medium of incubaiton, the least inactivation being seen in pooled human serum and the most in phosphate buffer at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 8 publications
0
18
0
2
Order By: Relevance
“…DISCUSSION Aminoglycosides have been used with extended-spectrum penicillins to provide wider antibacterial coverage against gram-negative bacilli through a synergistic effect (2,3,16,25,31,32). It is known, however, that the combined use may result in chemical inactivation of the aminoglycoside, leading to a loss in antibiotic activity (12,28). In vitro studies have demonstrated that the rate of inactivation is related to the incubation period, temperature, presence of solutes, and ,-lactam concentration (6,11,12,(21)(22)(23).…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Aminoglycosides have been used with extended-spectrum penicillins to provide wider antibacterial coverage against gram-negative bacilli through a synergistic effect (2,3,16,25,31,32). It is known, however, that the combined use may result in chemical inactivation of the aminoglycoside, leading to a loss in antibiotic activity (12,28). In vitro studies have demonstrated that the rate of inactivation is related to the incubation period, temperature, presence of solutes, and ,-lactam concentration (6,11,12,(21)(22)(23).…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…It is known, however, that the combined use may result in chemical inactivation of the aminoglycoside, leading to a loss in antibiotic activity (12,28). In vitro studies have demonstrated that the rate of inactivation is related to the incubation period, temperature, presence of solutes, and ,-lactam concentration (6,11,12,(21)(22)(23).…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Chemical inactivation of 1-lactam and aminoglycoside antibiotics occurs in vitro (18). Phamacokinetic interactions between these two classes of antibiotics have been reported in patients with normal and impaired renal functions (3,10,11,14,19,25). Since cefepime, as a 3-lactam, could be used in such a combination therapy, it was deemed * Corresponding author.…”
mentioning
confidence: 99%
“…Amikacin's stability against inactivation has been shown previously (5,6,8,13,15). We further demonstrated that heparin at a concentration as high as 100 U/ml did not interfere with the determination of isepamicin levels by automated FPI immunoassay when compared with 0.5% EDTA as an anticoagulant control.…”
Section: Discussionmentioning
confidence: 89%